Multi-year dynamics of the Aedes albopictus occurrence in two neighbouring cities in the Alps. Issue 1 (11th July 2023) - Lencioni, V.; Bertola, F.; Franceschini, A.; Ferrarese, U.; Zandonai, F.; Stancher, G.; Spitale, D.
Abstract: The invasive tiger mosquito Aedes albopictus is a serious nuisance for people due to its biting and potential for disease transmission, even in Italian mountain regions. In this work, we examined its occurrence dynamic from the first invasion in two Alpine cities, Rovereto and Trento, only 25 km apart. Mosquito's distribution was assessed using ovitraps, from mid-May to end-October, from its first reported occurrence, i.e. 2001 in Rovereto and 2010 in Trento. In both cities, ovitraps were located in seven habitat types: gathering places, residential areas, urban parks, car parks, near watercourses, industrial areas and croplands. The annual average temperature and precipitation were similar in the two cities from 2001 to 2020. We had hypothesized that the seasonal and annual differences in egg number between both cities would be limited. Significant linear and positive relationship was found between the average number of eggs and air temperature in both the cities, but with a steeper slope in Trento. In addition, the average number of eggs per ovitrap was higher in Trento than in Rovereto (average 50.3 vs 14.2). None of the considered risk factors (climate, habitat type) explained such difference in abundance between cities. Indeed, based on the temperature, the expectation was to find fewer eggs in Trento being cooler than Rovereto during 2010–2020 (the average in the period of activated traps was, respectively, 19.2 vs 19.7°C). Thus, we argue that other anthropogenic factors, such as different control activities (adulticide treatments were carried out solely in Rovereto), might explain the difference in egg abundance found between cities. A specific experimental design to evaluate treatment effect might validate our hypothesis (e.g. apply adulticides during the surveillance period, with treatments applied at regular distances from the ovitraps and with a specific periodicity to compare adult and egg abundance). Highlights: Ae. albopictus invaded two alpine cities 25 km apart with a lag of 12 yrs Temporal trend of egg abundance was positively correlated with temperature in both cities Ae. albopictus was more abundant in gathering places in urban areas The colder city (Trento) was the more infested Control activities carried out in Rovereto might explain difference in abundance between the two cities